Ageing body in the public discourse - Rapolienė, Gražina; Juozulynas, Algirdas (Sociologija. Mintis ir veiksmas, 2009)
Based on biomedical view bodily ageing in gerontology traditionally was associated with biological decline. Theorists of social gerontology recently noticed certain ambiguity of biomedical age discourses: between statements that ageing is universal, natural on one hand, and the proposed means for its „treatment“ on the other. The objective of the article is to discuss results of an investigation on representation of ageing body in Lithuanian mass media. The method used is qualitative content analyse using Hamlet data analysis software. Research data: publications mentioning bodily ageing in the internet portal “Delfi” (Lithuanian version) 2007.01.01 – 2007.12.31. The analysis of publications confirms theoretical insights showing that two interconnected topics are dominant in the public discourse: medical knowledge and body care. Ageing of body is associated with decline, destruction and risk to health, so ageing body is socially constructed asmarginal.
Keywords: body; ageing; mass media; disciplinary power; reflective project of the Self